THE DEFINITION OF THE SUNNAH ACCORDING TO ISMAILISM: A CRITICAL READING - Mahmoud, Ramy (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2021)
This research discusses the understanding of the sunnah according to Ismailism. The understanding of the Sunnah has been dominated by the definition of sunnah according to Sunni, the characteristic of Sunni in understanding the concept of sunnah by using Sunnah as a source of Islamic law and also giving more attention to the ahl bayt and also to the Sahaba. This notion is different from Shi’ah’s thought that only believes in ahl bayt, regardless of Sahaba. The difference between the two groups in seeing the degree of Sahaba makes the deferent of sunnah among them. By researching some of the of Ismailism’s thought in the definition of sunnah, this study is expected to contribute ideas related to Ismailism’s method in understanding the sunnah, and in judging the authenticity of sunnah, and to analyze the consistency of application to the sunnah according to Ismailism. This research shows that Ismailism followed esoteric approach to understand the concept of sunnah. This approach causes the sunnah position is not prioritized in the scientific structure of Ismailism. The reason for the small concern in Ismailism’s thought towards the Sunnah is basically started from their understanding about the verses of the Holy Qur’an, and their esoteric interpretation corresponds to the pillars of Ismailism. Keywords: Ismailism, Sunnah, Sunni, Shi’a, Critical Reading